Follow‐up evaluation of a web‐based pediatric brain tumor board in Latin America. Issue 9 (18th May 2021) - Rosabal‐Obando, Mariel; Osorio, Diana S.; Lassaletta, Alvaro; La Madrid, Andrés Morales; Bartels, Ute; Finlay, Jonathan L.; Qaddoumi, Ibrahim; Rutkowski, Stefan; Mynarek, Martin
Abstract: Background: Since 2013, pediatric oncologists from Central and South America discuss neuro‐oncology cases with experts from North America and Europe in a web‐based "Latin American Tumor Board" (LATB). Here, we evaluate the feasibility of recommendations rendered by the Board. Methods: An electronic questionnaire was distributed to physicians who had received recommendations between October 2017 and October 2018. Physicians were asked regarding the feasibility of each recommendation given during the LATB discussion. Baseline case characteristics of all presented cases were obtained from anonymized minutes. Results: Of the 142 patients discussed, data on 103 patients from 15 countries were available, corresponding to 283 recommendations. Physicians followed 60% of diagnostic procedural recommendations and 69% of therapeutic recommendations. The most difficult recommendations to follow were genetic and molecular testing, pathology review, chemotherapy, surgery, and molecular targeted therapies. Histological diagnoses changed in eight of 18 cases in which a pathology review was undertaken. Fifty‐four percent of the recommendations that could not be implemented were considered not feasible in the specific context of the patient, while 31% were not implemented due to a decision of the medical staff or the parents (15% not specified). However, 96% of respondents considered the recommendations useful. Conclusion: Recommendations were frequently perceived as useful, and were applicable in the participating institutions. Nevertheless, limitations in availability of diagnostic procedures and treatment modalities affected the feasibility of some recommendations. Tele‐oncology tumor boards offer physicians from low‐ and middle‐income countries access to real‐time, high‐level subspecialist expertise and provide a valuable platform for worldwide information exchange.